2017
DOI: 10.1039/c6ra28755g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition of nickel graphene composite coatings: effect of deposition temperature on its surface morphology and corrosion resistance

Abstract: The present work describes the fabrication of Ni–graphene composite coatings on carbon steel at different deposition temperatures (15 °C, 30 °C, 45 °C and 60 °C, respectively) by an electrochemical codeposition method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
67
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(77 citation statements)
references
References 50 publications
6
67
0
4
Order By: Relevance
“…Chembat et al 30 found the R a of the bare NiTi alloy around 1.7 ± 0.1 nm. Similarly, Abdul et al 31 studied on the graphene composite coatings on carbon steel and found the surface roughness (Ra) were 34 to 150 nm according to deposition temperature where they measured using AFM. The difference in R a values could be different due to the difference in the composition.…”
mentioning
confidence: 98%
“…Chembat et al 30 found the R a of the bare NiTi alloy around 1.7 ± 0.1 nm. Similarly, Abdul et al 31 studied on the graphene composite coatings on carbon steel and found the surface roughness (Ra) were 34 to 150 nm according to deposition temperature where they measured using AFM. The difference in R a values could be different due to the difference in the composition.…”
mentioning
confidence: 98%
“…The as prepared rGO shows a broad 2θ peak at 24.29 in (002) diffraction plane associated with reduced graphene oxide (rGO) of an interplanar distance 0.36 nm calculated by the Bragg's equation. This is due to the introduction of oxygenic functional groups and trapped water molecules between the graphite layers . During the anchoring of TMSPA, PAS and metal complex on the rGO surface, the diffraction peak of rGO do not disappear, indicating the structure of rGO is retained during the functionalization.…”
Section: Resultsmentioning
confidence: 99%
“…EIS tests are performed in 0.6M NaCl solution to study the anti-corrosion properties of the composite coatings obtained at different immersion times [12,28]. Figure 2 a-c. exemplified the Bode, phase angle and Nyquist (in situ) plots of substrate and composite coatings prepared at 30 mA cm -2 without and with 0.2g L -1 at different immersion times.…”
Section: Effect Of Graphene Concentration (Gns)mentioning
confidence: 99%
“…Meanwhile, the obtained EIS spectra of coatings deposited in absence of GNS showed narrow semicircles. In fact, the diameter of the semicircles decides the anti-corrosion property of coatings and the larger diameter ensures the better corrosion resistance [12]. Potentiodynamic polarization data (Table 2 a&b, Fig.…”
Section: Effect Of Graphene Concentration (Gns)mentioning
confidence: 99%
See 1 more Smart Citation